HYPERTENSION SELF-MANAGEMENT DIGITAL SYSTEM: IS DRUG SELF-REPORTING RELIABLE?. (June 2018) - Nogueira, J. Lima; Postel-Vinay, N.; Steichen, O.; Battaglia, C.; Bobrie, G.; Amar, L.
Abstract : Objective: e-health technology offers new possibilities for the self-management of home blood pressure measurements (HBPM). Hy-Result is a validated rule management system designed to help users to comply with the HBPM protocol and self-interpret their HBPM readings. The algorithm takes in account HBPM readings and patient characteristics and produces a PDF file with an automatized interpretation of the BP levels and educational information in plain language. When entering data (including risk factors and comorbidities), the patient can provide his current antihypertensive treatment in a non-mandatory free text field and send his report to the physician or nurse. We assessed the accuracy of the treatment self-reported by system users. Design and method: Observational, cross-sectional, retrospective study. Included patients consulting in an ESH excellence centre who had used the web system and E-mailed their PDF report to the centre. We checked the accuracy of the self-reported treatment (number of drug classes, name, dosage, number of daily intakes) compared to the medical prescription recorded in the medical file. Results: Ninety four patients (35% females, average age 53, 3) e-mailed their PDF reports; 10 reports were excluded because treatment was not self-reported (4) or not recorded during the consultation (6). Full concordance on the 4 criteria was 73% for the remaining 84 patients (Table). Errors were mostly related to dose and number of drug classes (omissions due to single-pill combinations). Figure. No caption available. Conclusions: When using Hy-Result, 90/94 (96%) of the patients self-reported their anti-hypertensive treatment in the electronic formulary. The number of drug classes, names, doses and daily intakes was perfectly concordant in 73 % of patients. Errors detected were related to number of drug classes and dose, mostly due to single-pill combinations. The majority of patients using the Hy-Result system e-mailed reliable information about their treatment. Patient empowerment for telemonitoring web based service is promising.